The U.S. external debt: risks and prospects for developing the strategy of the U.S. external debt management - Andrii Pin (Cхід)
According to the modern widespread approaches to the nature of external debt and its effects on economic processes, debt financing is among the distinctive features of the liberalization-oriented world of nowadays. Accordingly, unrestricted capital flows signify orientation at macroeconomic balance, since under the conditions when administrative barriers are absent capital distribution is even and symmetric, enabling leveling of factor prices. Associated with these arguments is a claim that prices of goods and services do not indicate non-negligible fluctuations and a financial system gains economic agents' confidence. This research addresses the issues of the phenomenon of external debt and provides an insight into the U.S. external debt and its effects on both the U.S. and world economy. The findings show that the U.S. external debt is of no considerable threat to the world economy in the short-term, since the peace of the world's economic leader's growth exceeds that of debt servicing expenditures. However, an economic decline may turn the status-quo upside down, since the country may face inability to raise enough funds in time to discharge its financial liabilities, especially to non-residents.